3, 4-Dihydroxyphenylacetic acid is a predominant biologically-active catabolite of quercetin glycosides. (November 2016) - Tang, Yue; Nakashima, Sayaka; Saiki, Shunya; Myoi, Yui; Abe, Naomi; Kuwazuru, Shoko; Zhu, Beiwei; Ashida, Hitoshi; Murata, Yoshiyuki; Nakamura, Yoshimasa
Abstract: Since dietary flavonoid glycosides, including quercetin 4′-glucoside from onion, are poorly absorbed from the gastrointestinal tract, they are converted into smaller phenolic acids, which can be absorbed into the circulation. The purpose of this study was to compare the effects of the major phenolic acid catabolites of quercetin 4′-glucoside, including 3, 4-dihydroxyphenylacetic acid (DOPAC), 3-hydroxyphenylacetic acid, 3, 4-dihydroxybenzoic acid (protocatechuic acid) and hippuric acid, on the antioxidant activity and phase II cytoprotective enzyme induction in vitro . Both DOPAC and protocatechuic acid, having a catechol moiety, exhibited both DPPH radical scavenging and superoxide dismutase-like activities, whereas 3-hydroxyphenyl acetic acid and hippuric acid did not. DOPAC also more potently enhanced the gene expression of several phase II drug-metabolizing enzymes than the other phenolic acid catabolites. DOPAC significantly inhibited the hydrogen peroxide-induced cytotoxicity in hepatocytes with the enhancement of the total glutathione S-transferase activity. In conclusion, DOPAC may play a key role in the antioxidative potential of the colonic lumen after the ingestion of the quercetin glycoside-rich onion. Graphical abstract: Highlights: DOPAC was identified as a predominant bioactive catabolite of quercetin glycosides. DOPAC potently enhanced the gene expression of phase II detoxification enzymes. DOPAC significantly inhibited the H2 O2 -induced cytotoxicity in hepatocytes. DOPAC plays a key role in antioxidative potential of the ingested quercetin.